prove that 2sinxcosx-cosx/1 -sinx+sin^2x-cos^2x=cotx

1 answer

LHS = (2sinxcosx-cosx)/(1-sinx-cos^2x+sin^2x)
= (2sinxcosx-cosx)/(sin^2x+cos^2x-sinx-cos^2x+sin^2x)
= (2sinxcosx-cosx)/(2sin^2x+cos^2x)
= cosx(2sinx-1)/sinx(2sinx-1)
= cosx/sinx
= cotx
=RHS
Similar Questions
  1. Prove:sin2x / 1 - cos2x = cotx My Attempt: LS: = 2sinxcosx / - 1 - (1 - 2sin^2x) = 2sinxcosx / - 1 + 2sin^2x = cosx / sinx - 1 =
    1. answers icon 5 answers
  2. Verify the identity .(cscX-cotX)^2=1-cosX/1+cosX _______ sorry i cant help you (cscX-cotX)=1/sinX - cosX/sinX = (1-cosX)/sinX If
    1. answers icon 0 answers
  3. My previous question:Verify that (secx/sinx)*(cotx/cscx)=cscx is an identity. (secx/sinx)*(cotx/cscx) = (secx/cscx)(cotx/sinx) =
    1. answers icon 2 answers
  4. 1. Prove the identity:cosx/1-tanx+sinx/1-cotx=sinx+cosx2.Prove the identity: cosx/1+sinx+1+sinx/cosx=2secx
    1. answers icon 0 answers
more similar questions